An annotated checklist of the Branchiopoda (Crustacea) of the Dutch Caribbean islands - Soesbergen, Martin; Sinkeldam, Jos (Zootaxa, 2019)
The launch of the Dutch Caribbean Species Register by Naturalis Biodiversity Center (2017)—https://www.dutchcaribbeanspecies.org/—raised the question of which branchiopods originate from this part of the Netherlands. To answer this question, surveys of literature and of the Naturalis collection were conducted. The additional samples (collected in 2003–2005 and 2008) were analyzed. We present an annotated checklist of the Branchiopoda of the Dutch Caribbean. The Kingdom of the Netherlands includes the Dutch mainland and six Caribbean islands. From the Caribbean part of the kingdom, an annotated list of all known species is given. Fifteen taxa and three genera have been encountered and the species are discussed. To date, six species of large branchiopods and nine species of cladocerans are known. Two more genera of cladocerans have been found. One species is endemic to Bonaire.